The Impact of AI Adoption on Customer Perceived Value, Satisfaction, and Loyalty in Social Commerce - Valentino Aris; Bobur Sobirov; Haris Maupa; Andi Ruslan; Arini Lestari (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study investigates how AI-based personalization, marketing analytics capability, and perceived privacy assurance influence customer loyalty in social commerce and whether these effects operate through perceived value and customer satisfaction. Research Methodology: A cross-sectional online survey was administered to 510 active social commerce users in South Sulawesi, Indonesia, to collect data. The hypothesized relationships and mediation effects were examined using PLS-SEM. Results: AI-based personalization significantly increased customer satisfaction and loyalty but had no significant effect on perceived value. Marketing analytics capability significantly strengthens perceived value; however, it has no significant direct effect on satisfaction or loyalty. Perceived privacy assurance positively affects perceived value, satisfaction, and loyalty. Both perceived value and customer satisfaction significantly enhance the loyalty. The mediation results indicate that marketing analytics capabilities indirectly strengthen loyalty via perceived value, whereas privacy assurance strengthens loyalty via both perceived value and customer satisfaction. AI-based personalization primarily drives loyalty through customer satisfaction. Conclusions: Customer loyalty in AI-enabled commerce is reinforced through complementary cognitive and affective pathways. Limitations: The findings are constrained by the cross-sectional design, self-reported data, and single-region sample. In addition, the privacy construct reflects assurance-oriented perceptions rather than anxiety. Contributions: This study clarifies the distinct roles and indirect mechanisms through which personalization, analytics capabilities, and privacy perceptions shape loyalty in social commerce.